Langman's medical embryology - Sadler, T. W. (Thomas W.) (Philadelphia, Wolters Kluwer, 2024)
"Every student will be affected by pregnancy, either: 1. Directly from their own gestation, since adverse exposures during their mother's pregnancy can have lasting healthcare effects postnatally; 2. having their own child; 3. having a patient who is pregnant"--
Includes index.
Catalography
Keywords: Embryonic Development; Fetal Development; Congenital Abnormalities